Nilai Karakter Cinta Tanah Air Dan Gotong Royong Pada Kearifan Lokal Manugal Sebagai Sumber Belajar Ips Di Sekolah Dasar - Rahmad Rahmad (MENDIDIK: Jurnal Kajian Pendidikan dan Pengajaran, 2021)
The purpose of this study was to instill the character values of Love for the Homeland and Mutual Cooperation in the local wisdom of Manugal as a source of social studies learning. The research method used is descriptive qualitative. Data collection techniques are observation, interview and document study. Data analysis techniques used are reduction, display and conclusion drawing. The results show that the value of the character of manugal wisdom in the form of love for the homeland can be integrated as a socialstudies learning resource in Class IV in Basic Competence (KD) 3.2 Identifying social, economic, cultural, ethnic and religious diversity in the local province as the identity of the Indonesian nation, as well as its relationship with space characteristics. Teachers use local wisdom as a source of learning so that students easily understand the value of love for the homeland through local wisdom by loving their own culture that still exists to be maintained and preserved as the younger generation. The value of gotong royong can be integrated with social studies learning resources for class V in Basic Competencies 3.1 Identifying the geographical characteristics of Indonesia as an archipelagic/maritime and agrarian country and their influence on economic, social, cultural, communication and transportation life. The teacher instills the value of gotong royong through a rice seed planting event that is done together.